Development of the Islamic and Muhammadiyah Module of Integration K13 Supplement at SD/MI Muhammadiyah - Munardji; Nurul Amin (Tarbiyah Departement collaboration with AMCA, 2018)
Muhammadiyah Schools must have distinctive features that distinguish them from other schools. The distinguishing characteristic should be something of a positive nature so that it can make Muhammadiyah schools become excellent schools as mandated in the progressive educational interpretation. This should apply to all Muhammadiyah schools including Primary School or Madrasah Ibtidaiyah Muhammadiyah as the first and main formal education level. Thus SD / MI Muhammadiyah need to have distinguishing characteristics with other schools. Distinguishing features that can be the availability of teaching materials that are able to integrate the values ​​of Islamic and Muhammadiyah in a various fields of study including mathematics. So this research is aimed to develop teaching materials in the form of integration module of ke-Islaman and ke-Muhammadiyahan value on mathematics material of data processing chapter. This study is a developmental study by modifying Borg & Gall (1985) development steps into steps that include: (1) Need Analysis (2) Module Design; (3) Module Development; (4) Products / Outputs. The results show that module development steps can produce ready-to-use modules in Primary School or Madrasah Ibtidaiyah Muhammadiyah in East Java or Indonesia.